Histopathological study of genital organs in a naturally infected mare with dourine - B, Mungun-Ochir; U, Nyamdolgor; P, Baatarjargal; G, Soyolmaa; A, Altanchimeg (Mongolian Journal of Agricultural Sciences, 2019)
The present study aimed to investigate pathological lesions occurred in both central and peripheral nervous systems in mare infected naturally with dourine. Nine years old mare, which was positive by PCR, examination of reproductive organ swabs and immune chromatographic testing and showed visible neurological signs of dourine was selected in this study. Objective of this study was to examine the patho-morphological changes in all genital organs of a naturally infected mare with T. equiperdum. Sections were stained with Hematoxylin- Eosin or other special staining solutions, and then observed under light microscopy. Histopathology results: Slight infiltration of inflammatory cell into peripheral nerve was observed. There was fragmented nuclei like microorganisms within the nerve fiber in the Utero-ovary ligament. Vagina: While inflammatory cell infiltration was seen in the vaginal mucosa, micro abscesses were also seen in the superficial of mucosa. There was microorganism like exocytosis structure in the vaginal mucosa. There was perivascular and peripheral neural inflammatory cell infiltration in the vaginal deep layer. Inflammatory cell infiltration and myelin sheath degeneration were observed in the peripheral nerve of vulva and inflammatory cell infiltration, myelin sheath degeneration and microorganism or fragmented nuclei were observed in the peripheral nerve of vulva. Inflammatory cells infiltrated into the deep layer of vulva. Cross section of vagina nerve. CD20 positive cells (lymphocyte B) and CD3 positive cells (lymphocyte T) in nerve fibers Нийлүүлгийн өвчтэй гүүний эмгэг морфологийн судалгаа Хураангуй: Бидний судалгаанд полимеразын гинжин урвал (ПГУ) болон иммунохромотографийн түргэн тестээр (ИХТ) эерэг дүн үзүүлж, нийлүүлгийн өвчний мэдрэлийн илэрхий шинж тэмдэг үзүүлж буй 4 настай хээр гүүнд эмгэг анатомийн задлан шинжилгээ хийж, тархи, захын мэдрэлийн судлууд, дотор эрхтнүүд, арьс, тунгалгийн зангилаанууд болон үржлийн эрхтнүүдээс дээж авч, 10 хувийн буфержүүлсэн формалинд бэхжүүлэн, MNS 5451:2005 стандартын дагуу дээжийг боловсруулж, парафинд цутган, зүсмэгийг гематоксилин-эозиноор будаж, микроскопын шинжилгээ хийв. Өвчилсөн гүүний нүүрний зүүн талын мэдрэл саажиж, зүүн чих унжсан, дээд уруулын булчин баруун тийш мурийсан, доод уруулын булчин бага зэрэг саажсан зэрэг шинж тэмдэг үзүүлсэн байлаа. Үлэмж бүтцийн шинжилгээний дүнгээр гүүний зүүн талын дээд уруулын өргөгч булчин, доод уруулын буулгагч булчин хатанхайрсан, бусад эрхтнүүд болох элэг, уушги, зүрх, бөөр, дэлүү, үржлийн эрхтэнд эмгэг өөрчлөлт илэрсэнгүй. Бичил бүтцийн судалгааны дүнгээр бүхий л захын мэдрэлүүд, үржлийн зарим эрхтнүүдийн мэдрэлийг хамарсан мэдрэлийн ширхгийн эмгэгшил буюу нейропати илэрсэн болно. Энэхүү судалгааны дүн нь байгалийн нөхцөлд нийлүүлгийн өвчнөөр өвчилсөн гүүнд эмгэг гистологийн өөрчлөлтийг нарийвчлан судалсан анхны үр дүнгүүдийн нэг юм. Түлхүүр үг: Гистологи, лимфоцит, иммуногистохими